Two Ways of Understanding Persons: A Husserlian Distinction - Sara Heinämaa (Rosenberg & Sellier, 2019)
This paper clarifies the distinction that Edmund Husserl makes between two different ways of understanding other persons, their actions and motivations: the experiential or empirical way, on the one hand, and the genuinely or authentically intuitive way, on the other hand. The paper argues that Husserl’s discussion of self-understanding clarifies his concept of the intuitive understanding of others and allows us to explicate what is involved in it: not just the grasping of the other’s actual motivations of action but also the grasping of her motivational possibilities. The paper ends by discussing the dynamic character of the personal subject.